Isolated terminal limb reduction defects: Extending the clinical spectrum of Adams–Oliver syndrome and ARHGAP31 mutations. Issue 6 (25th March 2014) - Isrie, Mala; Wuyts, Wim; Van Esch, Hilde; Devriendt, Koenraad
<x xml:space="preserve">Abstract</x> Adams–Oliver syndrome (AOS; OMIM 100300) typically comprises a combination of congenital scalp defects and terminal transverse limb defects. Recently, mutations in ARHGAP31 and RBPJ have been found causing autosomal dominant forms of AOS. We describe a four‐generation pedigree with isolated terminal limb defects and a truncating mutation in ARHGAP31. This finding underscores the relevance of sequencing ARHGAP31 in similar cases of isolated limb defects, irrespective of the presence of a complete AOS phenotype. We also highlight the variability of clinical features among mutation carriers, ranging from severe reduction defects to mild as well as clinically unaffected cases suggesting reduced penetrance. © 2014 Wiley Periodicals, Inc.